2005
DOI: 10.1111/j.1541-9215.2005.04653.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Thyroid Hormone Levels in Acute Myocardial Infarction: Just an Epiphenomenon?

Abstract: The purpose of this study was to investigate whether thyroid hormone levels have any predictive value for mortality in patients presenting to the emergency department with acute myocardial infarction (AMI). Three groups of patients admitted to the emergency department within the 11-month study period were considered eligible: 95 patients with chest pain and proven AMI, 26 patients with chest pain and no AMI, and 114 patients who served as controls with no evidence of any major disease. Cardiac enzymes and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The conclusion was that triiodothyronine and lower free thyroxine appeared to be independent prognostic factors in patients with AMI. 1 In our study, we showed a trend towards higher levels of troponin and TSH. However, correlation until this moment was not significant.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…The conclusion was that triiodothyronine and lower free thyroxine appeared to be independent prognostic factors in patients with AMI. 1 In our study, we showed a trend towards higher levels of troponin and TSH. However, correlation until this moment was not significant.…”
Section: Discussionsupporting
confidence: 58%
“…Another study 1 in 2005 investigated whether thyroid hormone levels had any predictive value for mortality in patients presenting to the emergency department with AMI. Three groups of patients admitted to the emergency department within the 11-month study period: 95 patients with chest pain and diagnosed AMI; 26 patients with chest pain and no AMI; and 114 controls with no evidence of any major disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Independent of time-course, type and severity, a low T3 state may serve as an adaptive mechanism which reduces metabolic demands by reducing the catabolic processes of the disease 8 . A low T3 syndrome was a frequent finding in patients with cardiac pathology and without a history of thyroid dysfunction, particularly among patients with HF, AMI, and those following cardiac surgery [15][16][17][62][63][64][65] . However, the exact point of occurrence of THs alterations, after an ACS, is not clearly understood 2,[66][67][68] .…”
Section: Discussionmentioning
confidence: 99%
“…The times and duration of hospitalization were also hypothesized to reflect the severity of the disease to some extent; hospitalization time was longer among survivors (7.46±4.01 days) compared to non-survivors (6.86±3.30) ( 36 ). However, no significant correlations of prognosis with times of hospitalization and duration of hospital stay were identified.…”
Section: Discussionmentioning
confidence: 99%